A Comparative Analysis of Space Vector Modulation-Based Common Mode Voltage Reduction Strategies in a Modular Multilevel Converter - Chengjun Tang; Jian Zhao; Torbjorn Thiringer (IEEE Access)
In various variable speed applications with power converters, failures in the bearings caused by common mode voltage (CMV) have been frequently reported. This study investigates space vector modulation (SVM)-based strategies for reducing CMV in a modular multilevel converter (MMC). Two strategies for CMV reduction, complete and partial, are examined. The study compares the impact of these strategies on feasibility, total losses, and current total harmonic distortion (THD). Both simulation and experimental results are analyzed, with experiments conducted on a wind turbine emulator driven by a five-level MMC. The findings demonstrate that both strategies can effectively limit CMV amplitude compared to cases without any CMV reduction strategy. The partial CMV reduction strategy, while resulting in a 6.7% increase in switching loss, offers the lowest current THD (0.73%). The complete CMV reduction strategy achieves near-zero CMV and reduces switching loss by 3.9%, but at the cost of the highest current THD (1.81%) and limited DC-link voltage utilization. Experimental results confirm the significant impact of CMV on main bearing performance, as both CMV reduction strategies can reduce the bearing current amplitude and the number of bearing current events. Specifically, the partial CMV reduction strategy extends the bearing lifetime by a factor of 49, while the complete CMV reduction strategy extends it by a factor of 416, both relative to no CMV reduction. These results underscore the effectiveness of CMV reduction strategies in mitigating bearing currents in modern power electronics-based electric drives.